Application of mesoporous silica particles as an additive for controlling rheological, thermal, and filtration properties of water-based fluids - Fookes, Federico Adrian (2024)
Mesoporous silica particles (MSP) have received increasing interest for various applications because of their unique features such as controlled pore size, low density, high chemical and thermal stability, and high surface area. In this study, MSP was applied as an additive in water-based drilling fluids (WBMs). The effect of MSP on the rheological, thermal, filtration, and structural properties of WBMs was investigated. The results were compared with those of analogous fluids containing conventional nonporous silica particles (SSP). Rheological assays showed shear-thinning and viscoelastic behavior, which were more noticeable for fluids including MSP. It was observed that low concentrations of MSP (0.25 %wt) can achieve the same rheological properties as the fluids with higher SSP content (up to 0.5 %wt). The rheological properties of SSP-containing fluids were not significantly affected by the presence of NaCl or aging tests. The theoretical Herschel–Bulkley model represents the rheological behavior of WBMs. The MSP-based WBMs exhibited better filtration properties before aging. The microstructures of the WBMs were analyzed using Scanning Electron Microscopy (SEM). A homogeneous distribution of SSP in the WBMs was observed, while particle agglomeration was observed in WBMs containing MSP. In addition, surface interactions were studied to elucidate the interactions between particles and fluid constituents. The surface interaction, assessed through ζ-potential and FTIR analysis, revealed that the binding affinities of BT, PAC, and XGD with MSP were augmented compared to their individual values. Based on the experimental results, MSP constitutes a promising alternative as an additive for the design of WBMs.